Dapog Paddy seedling raising method - Kapur, Lalit; Thakor, R F (Indian Farming, 2020)
Field assessment trials were conducted in Valsad district during kharif 2017 and kharif 2018 revealed that healthy paddy seedlings of paddy can be easily raised in small area near homestead within 14 to 17 DAS with low cost dapog nursery. Dapog method safeguards against deterioration of soil health and air pollution created by open burning of crop material and cow dung cake on field for land preparation to make traditional aadar flat bed nursery. Dapog method of raising paddy seedling has a potential to sustain soil health and improve productivity and profitability of paddy crop cultivation.